Comparison of space radiation GCR models to AMS heavy ion data. (August 2019) - Whitman, Kathryn; Norbury, John W.; Lee, Kerry; Slaba, Tony C.; Badavi, Francis F.
Abstract: Galactic cosmic rays (GCR) are a constant source of radiation that constitutes one of the major hazards during deep space exploration missions for both astronauts and hardware. In this work, GCR models commonly used by the space radiation protection community are compared with recently published high-precision, high-resolution measurements of cosmic ray lithium, beryllium, boron, carbon, nitrogen, and oxygen fluxes along with their ratios (Li/B, Li/C, Li/O, Be/B, Be/C, Be/O, B/C, B/O, C/O, N/B, N/O) from the Alpha Magnetic Spectrometer (AMS). All of the models were developed and calibrated prior to the publication of this AMS data, therefore this is an opportunity to validate the models against an independent data set. This paper is a compliment to the previously published comparison of GCR models with AMS hydrogen, helium, and the boron-to-carbon ratio (Norbury et al., 2018).